Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Temperature stabilizes rough Au/Ge(001) surface reconstructions - Seino, Kaori; Sanna, Simone; Schmidt, Wolf Gero (Surface Science)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Influence of strong screening effect on the perpendicular- polarized linear excitonic absorption spectra of semiconducting carbon nanotubes - Liu, Hong (The European Physical Journal B)

Single PTCDA molecules on planar and stepped KCl and NaCl(100) surfaces - Aldahhak, Hazem; Schmidt, Wolf Gero; Rauls, E. (Surface Science)

Diindenoperylene adsorption on Cu(111) studied with density-functional theory - Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Water adsorbate influence on the Cu(110) surface optical response - Baghbanpourasl, Amirreza; Schmidt, Wolf Gero; Denk, Mariella; Cobet, Christoph; Hohage, Michael; Zeppenfeld, Peter; Hingerl, Kurt (Surface Science)